EKSPLORASI PERAN MUSEUM SANG NILA UTAMA SEBAGAI MEDIA EDUKASI DAN REPRESENTASI CIRI KHAS BUDAYA RIAU - Dhiya saffanah.H; Chika Zaffa Azzahira; Chindy Hafitzah; Fitri Oktavian Lubis; Maria Novitasari Hutagalung; Rahmatul Ulfah; Zahratul Wahidah; Hambali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Museums play a crucial role as institutions that preserve the nation's collective memory, not only as repositories but also as educational and entertainment resources. This research focuses on the importance of enhancing cultural and historical understanding among the public, particularly the younger generation, in order to optimize the museum's function. Cultural understanding, encompassing knowledge, skills, and attitudes toward cultural heritage, is considered key to creating meaningful experiences and encouraging active involvement in cultural preservation. Regional museums, such as the Sang Nila Utama Museum in Riau Province, are ideal locations for developing this understanding. However, numerous challenges remain, such as a lack of interest from young people, ineffective promotion, complex bureaucratic processes, and limitations in technology implementation. Initial observations indicate that although the museum boasts unique and historically valuable collections, public knowledge (including that of students in Pekanbaru) about its role and existing collections remains very limited. This is due to the perception that museums are unattractive, a lack of comprehensive information, and limited digital accessibility. This situation contributes to the low number of visitors and the Riau community's weak understanding of their heritage. Therefore, strategic steps are needed to address these issues to maximize the museum's role in enhancing cultural understanding.